Harmonious Coexistence: Intercultural Communication Dynamics Between Legal Immigrants and Residents in Gading Serpong - Simbolon, Mardiana; Ummanah, Ummanah; Iswadi, Iswadi (CHANNEL: Jurnal Komunikasi, 2023)
This research delves into the intricate dynamics of intercultural communication within the context of legal immigration, focusing on the community of Gading Serpong. This study employs qualitative research methods to explore the multifaceted interplay of language, social norms, economic collaboration, and government initiatives in fostering harmonious relationships between legal immigrants and residents. Despite linguistic and cultural disparities, the residents of Gading Serpong exhibit a remarkable willingness to engage in dialogue, mutual understanding, and reciprocal respect. The study uncovers the pivotal role of collaborative efforts, inclusive educational practices, and responsible media portrayals in facilitating social integration. Furthermore, the proactive involvement of the local government and community initiatives contributes significantly to creating an inclusive environment, ensuring immigrants are valued members of society. The findings underscore the importance of sustaining efforts to promote ongoing dialogue, cultural awareness, and inclusivity, solidifying Gading Serpong as an exemplar of cultural harmony and diversity within the Indonesian context.